1996
DOI: 10.1080/03079459608419138
|View full text |Cite
|
Sign up to set email alerts
|

An experimental turkey rhinotracheitis (TRT) infection in breeding turkeys and the prevention of its clinical effects using live‐attenuated and inactivated TRT vaccines

Abstract: The experimental inoculation of 38-week-old turkey hens with a pool of field isolates of turkey rhinotracheitis virus (TRTV) induced a marked respiratory infection and a substantial drop in egg production. Administration of a live-attenuated TRT vaccine at 1 week of age did not protect the layers against respiratory infection, but provided good protection against the effects of challenge on laying performance. However, a combination of live priming followed by injection of inactivated vaccine provided excellen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 7 publications
1
31
0
1
Order By: Relevance
“…Live attenuated viruses are good vaccine candidates as they induce strong immune responses and protection (Murphy et al, 1988;Cook et al, 1996;Collins et al, 1999). Although it has been shown that vaccines developed against subgroups A and B protect against the US isolates (Cook et al, 1999), it is advisable to develop a homologous subgroup C vaccine to avoid the introduction of subgroups A and B into the US.…”
Section: Discussionmentioning
confidence: 99%
“…Live attenuated viruses are good vaccine candidates as they induce strong immune responses and protection (Murphy et al, 1988;Cook et al, 1996;Collins et al, 1999). Although it has been shown that vaccines developed against subgroups A and B protect against the US isolates (Cook et al, 1999), it is advisable to develop a homologous subgroup C vaccine to avoid the introduction of subgroups A and B into the US.…”
Section: Discussionmentioning
confidence: 99%
“…This was performed as described previously (Cook et al, 1996) , using a subgroup A strain, a subgroup B strain, or the Colorado isolate as antigen. Antibody titres of $ log27.0 were considered to be positive.…”
Section: Serologymentioning
confidence: 99%
“…In May 1996, a respiratory infection, characterized by coughing, rhinitis and sinusitis, was described in commercial turkeys in the state of Colorado, USA (Senne et al, 1997). Serum samples collected from these turkeys were examined in the UK for APV antibodies by enzyme-linked immunosorbent assay (ELISA), using a subgroup A strain of TRT as antigen (Cook et al, 1996), and low antibody titres to APV were detected in some of the sera. A virus was subsequently isolated from these turkeys (Senne et al, 1998a,b) and shown to have some antigenic relationship with existing TRT isolates (Cook et al, 1998a,b).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the influence on laying birds it is most significantly a respiratory disease of mainly young birds, especially in turkeys but also in chickens. Early vaccination straight after hatch by spray or aerosol is already widely practised in turkeys to protect the birds (Williams et al, 1991;Cook et al, 1996).…”
mentioning
confidence: 99%
“…Serological testing was carried out by enzyme-linked immunosorbent assay as described previously (Cook et al ., 1996). In this enzyme-linked immunosorbent assay, a subtype A virus was used as coating antigen, purified after two sucrose gradient steps.…”
mentioning
confidence: 99%